CRYSTAL STRUCTURES OF LAMPROPHYLLITE-2M AND LAMPROPHYLLITE-20 FROM THE LOVOZERO ALKALINE MASSIF, KOLA PENINSULA, RUSSIA - Krivovichev S.V.; Armbruster T.; Yakovenchuk V.N.; Pakhomovsky Y.A.; Men'shikov Y.P. (My University, 2003)
The crystals of lamprophyllite-2M and lamprophyllite-2O were found coexisting in an ussingite-microcline-sodalite veins in the Alluaiv Mt., Lovozero alkaline massif, in association with ussingite, aegirine, microcline, sodalite, albite, mangan-neptunite, vuonnemite, sphalerite, lomonosovite and betalomonosovite. The chemical composition of the polytypes corresponds to the formula (Sr1.18Na0.66Ca0.12)(Sigma1.96)Na(Na1.30Mn0.36Fe0.22Mg0.12)(Sigma2.00)Ti3O2(Si2O7)(2)(OH)(2). The structures of lamprophyllite-2M (C2/m, a=19.215(5), b=7.061(2), c=5.3719(15) Angstrom, beta=96.797(4)degrees, V=723.7(4) Angstrom(3)) and lamprophyllite-2O (Pnmn, a=19.128(4), b=7.0799(14), c=5.3824(11) Angstrom, V=728.9(3) Angstrom(3)) have been refined to R=0.040 for 688 reflections (\F-o\ greater than or equal to 4sigma(F)) and to R=0.084 for 571 reflections (\F-o\ greater than or equal to 4sigma(F)), respectively The structures of both polytypes are based on the HOH layer consisting of a central O sheet of edge-sharing Na(1)O-6, Na(2)O-6 and Ti(2)O-6 octahedra sandwiched between two heterophyllosilicate H sheets. The H sheet is built by corner-sharing of Ti(1)O-5 square pyramids and Si2O7 groups and consists of two types of rings of polyhedra: (i) six-membered rings (6R) formed by two Si2O7 groups and two TiO5 square pyramids and (ii) four-membered rings (4R) formed by two silicate tetrahedra and two TiO5 square pyramids. The Sr atom is located in the interlayer and is coordinated by six anions from 6R of the upper H sheet and four anions from 4R of the lower H sheet. The difference between monoclinic and orthorhombic lamprophyllites can be described in terms of different orientations of HOH layers. Whereas in lamprophyllite-2M, all HOH layers are in the same orientation, in lamprophyllite-2O, two adjacent layers are in different orientations.
Keywords: lamprophyllite; polytypism; Lovozero alkaline massif